Effect of Coral-Algal Interactions on Early Life History Processes in Pocillopora acuta in a Highly Disturbed Coral Reef System - Leong, Rick C.; Marzinelli, Ezequiel M.; Low, Jeffrey; Bauman, Andrew G.; Lim, Elton W. X.; Lim, Chin Y.; Steinberg, Peter D.; Guest, James R. (Frontiers in Marine Science, 2018)
Scleractinian corals are vulnerable to a range of environmental disturbances, but generally suffer the highest rates of mortality during early life-history stages, i.e., from larval settlement until a few months post-settlement. Variations in survival rates of corals during this period play a key role in structuring adult coral populations. Many coral reefs have experienced reductions in herbivory rates due to overfishing and consequent increases in macroalgae, however, the effect of increased coral-algal interactions may vary between coral life-history stages and among locations. Therefore understanding the relative importance of different drivers of mortality across early life-history stages, under a range of environmental conditions, is essential to effectively manage and restore coral reefs. To date, however, relatively few studies few have a) examined coral-algal interactions across several early life-history stages (i.e. from planulae to juvenile colonies) and b) done so in highly disturbed reefs close to large urban centres. We investigated the effect of algal-coral-herbivore interactions on early life history stages in the coral Pocillopora acuta on coral reefs off mainland Singapore, a heavily disturbed “urbanised reef environment”. Larval settlement rates were estimated in the presence of six macroalgal species ex situ. The effect of direct interaction with two macroalgal species on newly settled spat was examined in situ and the effect of reduced herbivory was tested with exclusion cages on naturally settled 9-month old juveniles in situ. We found significant reductions in P. acuta settlement in the presence of four macroalgal species. Newly settled spat of P. acuta had significantly lower survivorship when in contact with Sargassum sp. on the reef crest but not with Bryopsis sp. on the reef flat. Herbivore exclusion reduced survivorship of juvenile corals, which was associated with increased sediment accumulation, but not with algal biomass. Our results suggest coral recruitment on heavily disturbed reefs can be impacted by species-specific macroalgal effects via reduced settlement on ephemeral substrata and reduced survivorship when in direct contact with Sargassum sp. Furthermore, recruitment may be negatively impacted by reductions in herbivory, possibly via increased abundance of epilithic algal matrix leading to sediment trapping.